EVALUATION OF REED RECOURSES IN THE LUBANS LAKE AND SUBSTANTIATION OF THEIR USE IN ENERGY PRODUCTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents the results of evaluation of reed resources in Latvia largest lake Lubans and for comparison in the small lake Kovshu. The investigation proved that resources of reeds are sufficient to replace from 2 to7 thousand tons of different fossil fuel. Measured reed physical properties- carbon quality, ash content and structure, moisture content proved that reeds are profitable fuel for heat energy production.